METHODS OF MULTIPLE CODE TRANSFORMATION - Гамаюн, В. П.; Кучма, С. В. (Proceedings of National Aviation University (archive), 2021)
A method of multi-line code conversion with bitwise sum equalization is proposed.The distribution of bitwise sums is described. The obtained statistical data on the results of equalization of bitwise sums are given.